Associations between eating expectancies and Eating disorder symptoms in men and women. (1st October 2019) - Brosof, Leigh C.; Munn-Chernoff, Melissa A.; Bulik, Cynthia M.; Baker, Jessica H.
Abstract: Eating expectancies, or learned expectations that an individual has about eating, prospectively predict eating disorder (ED) symptoms. Most studies examining eating expectancies have focused on one or two eating expectancies and their relation with bulimic symptoms. In addition, these studies have been conducted mostly in women. Thus, it is unclear whether: 1) associations between eating expectancies and ED symptoms vary between men and women, and 2) extend to ED symptoms other than bulimic symptoms. The current study ( N  = 197 undergraduate men and 246 undergraduate women) investigated sex variance in a model of eating expectancies and ED symptoms, including factors associated with ED symptoms (i.e., negative urgency, negative affect, alcohol use, drug use, and body mass index). Sex variance was tested using path analysis in a model including eating expectancies and associated factors, with excessive exercise, negative attitudes toward obesity, restricting, cognitive restraint, binge eating, purging, muscle building, and body dissatisfaction as dependent variables. Unconstrained (i.e., unconstrained paths across men and women) and constrained (i.e., constraining paths across men and women) models were tested. The unconstrained and constrained models differed significantly, indicating that the models varied by sex. For both sexes, eating expectancies were uniquely associated with ED symptoms. For men, Eating Manages Negative Affect was significantly associated with the most ED symptoms. In contrast, for women, Eating Leads to Feeling Out of Control was associated with the most ED symptoms. Previous findings regarding eating expectancies and ED symptoms in women may not generalize to men. Intervening on eating expectancies in a sex-specific way may help reduce specific ED symptoms.